(untitled) (Research, Society and Development, 2018)
This work aims to study the celebration of the centenary of the Law of October 15, 1827 in Rio Grande do Norte, based on the work of Nestor dos Santos Lima "A Century of Primary Education" and the Photo Album of the Historical Geographic Institute of Rio Grande do Norte: "Normal School" of 1927 that records the celebrations to the centenary of the Law, in the aforementioned State. The Law of 1827 instituted the public education in the country and determined that in all cities, towns and places more populous there would be as many schools of first letters were necessary. This research deals with a study of bibliographical and documentary revision, considering for the analysis the theoretical understandings of Nora on the places of memory and Le Goff about document-monument. In the process of understanding and investigating the study objective, we ask ourselves: how did the celebration of the centenary of the Law of October 15, 1827 in Rio Grande do Norte? Or, what was the purpose of Rio Grande do Norte in celebrating the centennial of the Law of October 15, 1827, since the work cited above was produced by order of the State itself? The partial results of the research indicate that this celebration constitutes a place of memory, placing the figure of Nestor dos Santos Lima at the center of the education history of Rio Grande do Norte, while producing a demarcation for the field of education, more specifically in primary education.